Differences in local anesthesia techniques of jet injectors and 3 cc spoits on children's pain perception in ishak al-hijrah foundation ambon - Labulawa, Irman; Thalib, Abdul (CV. Paperhome Indonesia, 2024)
Background: Body hygiene is one of the most important things to do in Islam, circumcision which is a sunnah recommended for every Muslim to avoid unclean on the male genitals which is a requirement in performing prayers. Objective: To determine the comparison of local anesthesia administration of circumcision patients with jet injectors and 3cc spoits on children's pain perception at Ishak Al-Hijrah Ambon Foundation. Method : The design of pretest and postest aims to determine the effect of the effect of the comparison of local anatesia of circumcision patients with jet injectors on the pain perception of children pre op circumcision at the Ishak Al-Hijrah Foundation Ambon. Results: showed that the pain response obtained from 7 respondents using 3cc spoit was 5 respondents with severe pain (71.5%), 1 respondent with moderate pain (14.2%) and 1 respondent with mild pain (14.2%). Pain response after administration with jet injector at Yayasan Ishak Al-Hijrah Ambon obtained from 7 respondents was 5 respondents with mild pain (71.5%), 1 respondent with moderate pain (14.2%). And 1 respondent with mild pain (14.2%). Conclusion: obtained differences in jet injector local anesthesia techniques with 3 cc spoit on children's pain perception at the Ishak Al-Hijrah Foundation Ambon.